Pseudomonas aeruginosa injection for the treatment of chyle fistula following neck dissection in thyroid cancer - Chen, Defeng; Zhu, Zhen; Jin, Qiufeng; Yuan, Junhui; Zhang, Xu; Fang, Qigen (Frontiers in Endocrinology, 2025)
ObjectiveTo present our experiences with Pseudomonas aeruginosa injection (PAI) for managing chyle fistula (CF) following thyroid surgery, with a focus on its efficacy and safety.MethodsWe conducted a retrospective, single-center study enrolling patients with CF. Patients were categorized into low- (~500 mL/d), moderate- (500-1000 mL/d), and high-output (>1000 mL/d) groups. The primary outcomes were the efficacy and safety of PAI.ResultsA total of 95 patients were included. Among them, eight with low-output CF, five with moderate-output CF, and 15 with high-output CF underwent PAI. Following PAI, a significant reduction in drainage volume was observed, resulting in the removal of 92.9% of drainage tubes by the third day post-treatment. Fever and pain of varying intensity were common adverse effects immediately after PAI. However, by the third day, no patients had a fever, and no moderate or severe pain was reported. Based on our findings, we propose that initial CF management should be stratified by drainage output. The majority of cases were effectively resolved using PAI and other non-surgical interventions, with reoperation reserved only for when conservative treatments failed.ConclusionPAI proved effective in resolving CF after unsuccessful prior non-surgical interventions following thyroid surgery, with minimal complications. Management of CF requires a tiered approach based on output levels.